Role of Forest Management Units in Managing the Crime of Illegal Logging - Shoviyanto Shoviyanto (Jurnal Hukum Khaira Ummah, 2021)
This study aims to determine the form and analyze law enforcement against illegal logging crimes in the process of tackling as well as to find out the obstacles faced and provide solutions in overcoming the crime of illegal logging according to KPH Pati Central Java related to forest management. This study uses a sociological juridical approach. Weak law enforcement against perpetrators of illegal logging. The policy of overcoming the crime of illegal logging in the KPH Pati area of Central Java is carried out with 2 (two) facilities, namely non-penal facilities and penal facilities. Non-penal means consist of 2 (two) patterns, namely the preemptive pattern and the preventive pattern. The penal tool uses a repressive pattern. The obstacles faced by KPH Randublatung in tackling the crime of illegal logging consist of external obstacles. The solution to the obstacles to the KPH Pati in Central Java is conducting outreach to local residents, conducting patrols, installing signposts that are prohibited from illegally cutting trees.